Synthesis of ZrN Film Via the Plasma Sputter-Type Negative Ion Source - Valmoria, Nico; Mendenilla, Alexander; Yambot, Miguel; Mena, Manolo; Ramos, Henry (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
A plasma sputter-type negative ion source is used in the production of high grade coatings of zirconium mononitride (ZrN) on copper substrate. It presents a new approach for the production of ZrN thin films. The ion source was operated in its target/gas mode. Zirconium metal is used as target and argon as the sputtering gas. Nitrogen is used as the reactive gas. Optimum conditions for the synthesis of ZrN for a number of process parameters like volume ratio of gases, discharge conditions, substrate heating, bias, and deposition time were determined. Experimental runs using between 20% and 30% of nitrogen (with argon constituting the other 70-80%) in a total gas filling pressure of 7.0 x 10-3 Torr and an hour of deposition showed the synthesis of good samples by visual inspection in view of the typical gold color of the film produced. The target potential was between 300V to 325V and the target current between 7 mA to 12 mA. Discharge voltage was at 40V giving a plasma current between 698 mA to 1070 mA for the range of target potentials. The substrate was cooled to 20°e. The resulting layers were characterized by surface analysis methods like X-ray diffraction (XRD), atomic force microscopy (AFM), and energy dispersive Xray analysis (EDAX). Films produced under these conditions exhibit the (100) and (200) peaks of ZrN obtained from the XRD analysis. The rms roughness from AFM were determined to range from 72 nm to 101 nm. Deposition rate was obtained at about 17 nm/min.
Keywords: ion source; plasma; thin film; target; substrate